(untitled) (PerCursos, 2021)
The usage of social media was significantly expanded in 2020, what made it necessary to analyze the geographical experience of networking and displacement in the pandemic. By increasing the use of digital technologies in our daily lives, due to the impossibility of fully enjoying the city, we have profoundly modified our physical, bodily and cultural relations with the city. The overlaps between the networks formed in the pandemic, with impact on the territory, and the virtual networks form hybrid spaces. Based on data from a doctoral research from the Postgraduate Program in Geography at the Federal University of Espírito Santo, Brazil, this study investigated the experience of mapping the networks of five women with community activities in the Centro district (downtown), in Vitória, Espírito Santo, symbolically and materially building another city. The premise is a knowledge process under construction, not necessarily linear or explicitly academic about the relationship between extensive and intensive mapping. The article addresses the relationship between body and city, mapping, displacement records and analysis of these hybrid spaces. In the conclusion, we rescued the extensive and intensive map relationship, the route built in the article and reflections on other possible paths for mapping.